Islet Transplantation and Encapsulation: An Update on Recent Developments (The Review of Diabetic Studies, 2023)
Human islet transplantation can provide good glycemic control in diabetic recipients without exogenous insulin. However, a major factor limiting its application is the recipient’s need to adhere to life-long immunosuppression, something that has serious side effects. Microencapsulating human islets is a strategy that should prevent rejection of the grafted tissue without the need for anti-rejection drugs. Despite promising studies in various animal models, the encapsulated human islets so far have not made an impact in the clinical setting. Many non-immunological and immunological factors such as biocompatibility, reduced immunoprotection, hypoxia, pericapsular fibrotic overgrowth, effects of the encapsulation process and post-transplant inflammation hamper the successful application of this promising technology. In this review, strategies are discussed to overcome the above-mentioned factors and to enhance the survival and function of encapsulated insulin-producing cells, whether in islets or surrogate β-cells. Studies at our center show that barium alginate microcapsules are biocompatible in rodents, but not in humans, raising concerns over the use of rodents to predict outcomes. Studies at our center also show that the encapsulation process had little or no effect on the cellular transcriptome of human islets and on their ability to function either in vitro or in vivo. New approaches incorporating further modifications to the microcapsule surface to prevent fibrotic overgrowth are vital, if encapsulated human islets or β-cell surrogates are to become a viable therapy option for type 1 diabetes in humans.